A national quality incentive scheme to reduce antibiotic overuse in hospitals: evaluation of perceptions and impact - Islam, J; Ashiru-Oredope, D; Budd, E; Howard, P; Walker, A; Hopkins, S; Llewelyn, M (Oxford University Press, 2018)
Background: In 2016/2017, a financially-linked antibiotic prescribing quality improvement initiative (AMR-CQUIN) was introduced across acute hospitals in England. This aimed for >1% reductions in Defined Daily Doses / 1000 admissions of total antibiotics, piperacillin/tazobactam and carbapenems compared with 2013/2014 and improved review of empiric antibiotic prescriptions. Objectives: To assess perceptions of staff leading antimicrobial stewardship activity about the AMR-CQUIN, the investments made by hospitals to achieve it and how these related to achieving reductions in antibiotic use. Methods: We invited antimicrobial stewardship leads at acute hospitals across England to complete a web-based survey. Antibiotic prescribing data were downloaded from the Public Health England Antimicrobial Resistance local Indicators resource. Results: Responses were received from 116/155 (75%) acute hospitals. Due to yearly increases in antibiotic use, most trusts needed to make >5% reductions in antibiotic consumption to achieve the AMR-CQUIN goal of 1% reduction. Additional funding was made available at 23/113 (20%) trusts, and in 18 (78%), this was <10% of the AMR-CQUIN value. Nationally, the annual trend for increased antibiotic use reversed in 2016/2017. In 2014/2015 year-on-year changes were +3.7% (IQR[-0.8, +8.4], +9.4%[+0.2, +19.5] and +5.8%[-6.2, +18.2] for total antibiotics, piperacillin/tazobactam and carbapenems respectively and +0.1%[-5.4, +4.0], -4.8%[-16.9, +3.2] and -8.0%[-20.2, +4.0] in 2016/2017. Hospitals where staff believed they could reduce antibiotic use were more likely to do so (p<0.001). Conclusions: Introducing the AMR-CQUIN was associated with a reduction in antibiotic use. For individual hospitals, achieving the AMR-CQUIN was associated with favourable perceptions of staff and not availability of funding.